Infantile Spasms Treated with Intravenous Methypredinsolone Pulse - HASSANZADEH RAD, Afagh; AMINZADEH, vahid (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Hassanzadeh Rad A, Aminzadeh V. Infantile Spasms Treated with Intravenous Methypredinsolone Pulse. Iran J Child Neurol. Spring 2017; 11(2):8-12. Abstract Objective Infantile spasms is diagnosed late even by expert pediatricians. Late diagnosis (later than 3 weeks) can have a negative effect on the long-term prognosis. We aimed to investigate infantile spasms treated with intravenous methylprednisolone pulse. Materials & Methods In this case series study, 20 infants with infantile spasms in 17-Shahrivar Hospital, Rasht, Iran were enrolled. Drugs were administered based on Mytinger protocol that included 3 days of methylprednisolone pulse and 56 days of oral prednisolone. The control of spasms and the omission of hypsarrhythmia in infants follow-up were the primary and secondary outcomes, respectively. Remission was indicated if the caregivers mentioned no spasms or >50% decrease regarding drug initiation for at least 5 consecutive days and the electroencephalography during sleep period noted the omission of hypsarrhythmia. Results Eleven female (55%) and 9 male (45%) patients with the mean age of 4.95±1.39 months were enrolled. Mean rapid remission was noted as 4.41±1.50 days. Twelve patients (60%) noted early remission. seizure was controlled in 3(15%) patients completely after 24 months. Five (25%) occasional seizures were noted controlled by routine anticonvulsant drugs after 24 months and 12 (60%) no response was mentioned. Most of the patients (65%) had cryptogenic etiology for infantile spasms. Uncontrolled seizure was mentioned after initial remission. Conclusion Methyl prednisolone is an appropriate drug based on easy administering, low cost, and its accessibility. References 1.Widjaja E, Go C, McCoy B, Snead OC. Neurodevelopmental outcome of infantile spasms: a systematic review and meta-analysis. Epilepsy Res 2015;109:155-62. 2. Mackay M, Weiss S, Adams-Webber T, Ashwal S, Stephens D, Ballaban-Gill K, et al. Practice Parameter: Medical Treatment of Infantile Spasms Report of the American Academy of Neurology and the Child Neurology Society. Neurology 2004;62(10):1668-81. 3. Abbas A, Elseed M, Hamed A, Mohamed IN. The role of oral prednisolone in the management of infantile spasms in resource-limited countries: experience from Sudan. Khartoum Med J 2016 Apr 5;7(3): 1012-18. 4. Riikonen R. A long-term follow-up study of 214 children with the syndrome of infantile spasms. Neuropediatrics 1982;13(1):14-23. 5. O’Callaghan FJ, Edwards SW, Alber FD, Hancock E, Johnson AL, Kennedy CR, et al. Safety and effectiveness of hormonal treatment versus hormonal treatment with vigabatrin for infantile spasms (ICISS): a randomised, multicentre, open-label trial. The Lancet Neurol 2017;16:33-42. 6. Pellock JM, Hrachovy R, Shinnar S, Baram TZ, Bettis D, Dlugos DJ, et al. Infantile spasms: a US consensus report. Epilepsia 2010;51(10):2175-89. 7. Hrachovy RA, Frost JD, Kellaway P, Zion TE. Double-blind study of ACTH vs. prednisone therapy in infantile spasms. J Pediatr 1983;103(4):641-5. 8. Delesalle F, Staumont D, Houmany MA, Breviere GM, Piette F. Pulse methylprednisolone therapy for threatening periocular haemangiomas of infancy. Acta Derm Venereol 2006;86(5):429-32. 9. Nguyen J, Fay A. Pharmacologic therapy for periocular infantile hemangiomas: a review of the literature. Semin Ophthalmol 2009: 24(3):178-184. 10. Mytinger JR, Quigg M, Taft WC, Buck ML, Rust RS. Outcomes in treatment of infantile spasms with pulse methylprednisolone. J Child Neurol 2010: 25(8): 948-53. 11. Azam M, Bhatti N, Krishin J. Use of ACTH and prednisolone in infantile spasms: experience from a developing country. Seizure 2005;14(8):552-6. 12. Lux AL, Edwards SW, Hancock E, Johnson AL, Kennedy CR, Newton RW, et al. The United Kingdom Infantile Spasms Study comparing vigabatrin with prednisolone or tetracosactide at 14 days: a multicentre, randomised controlled trial. The Lancet 2004;364(9447):1773-8. 13. Kossoff EH, Hartman AL, Rubenstein JE, Vining EP. High-dose oral prednisolone for infantile spasms: an effective and less expensive alternative to ACTH. Epilepsy Behav 2009;14(4):674-6.